Potential Benefits and Threads Arising from a Plant-Based Diet - Gąsiewska, Maria; Jancza-Smuga, Małgorzata (Korzyści i zagrożenia wynikające ze stosowania diety roślinnej, 2022)
A plant-based diet is a type of diet gaining more and more popularity. It is a elimination diet excluding all animal products and by-products. There are many reasons for switching from a traditional diet to a plant-based diet. This paper focuses on the four most prevalent reasons for switching diet: economical, health-related, ethical and ecological. The potential benefits and threats of a plant-based diet are also presented.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 27-40
Keywords: plant-based diet; vegan diet; vegetarian diet; dieta roślinna; dieta wegańska; dieta wegetariańska